Potential triggering factors associated with aneurysmal subarachnoid hemorrhage: A large single‐center retrospective study. Issue 7 (23rd June 2022) - Li, Runting; Chen, Xiaolin; Zhao, Yuanli
Abstract: Controlling blood pressure levels is critical to preventing intracranial aneurysm rupture, and a summary review of induced rupture events allows better health education for patients. We retrospectively reviewed all medical records of consecutive patients with aneurysmal subarachnoid hemorrhage (aSAH) admitted to Beijing Tiantan Hospital from 2015 to 2020. We collected patients' demographic information, aneurysm morphology, blood pressure level on admission, time to onset, and events at the time of aneurysm rupture to analyze the factors precipitating aneurysmal rupture. A total of 764 patients were enrolled for analysis, including 461 (60.3%) female patients and 303 (39.7%) male patients. The mean age of onset in this cohort was 55, and 465 (60.9%) patients had hypertension history. Autumn (245/764 [32.1%]) was the most frequent season for aneurysm rupture, and 07:00–12:59 (277/764 [36.3%]) was the most frequent time frame for aneurysm rupture. The five most prevalent events when aneurysm rupture happened were: (1) daily behaviors that may induce hypertension (181/764 [23.7%]), especially defecation or micturition (116/181 [64.1%]); (2) sporting (162/764 [21.2%]), especially high‐intensity sports (108/162 [66.7%]); (3) mood and mental factors (112/764 [14.7%]), especially arguing or quarreling (61/112 [54.5%]); (4) sudden postural changes (93/764 [12.2%]), especially getting up (69/93 [74.2%]); and (5) sleeping (72/764 [9.4%]). Patients should avoid behaviors that may cause fluctuations in blood pressure, including keeping warm during seasonal alternation, keeping their urine and defecation unobstructed, avoiding high intensity physical exercise, maintaining a happy mood, avoiding sudden postural changes, and should not bathe with too cold or too hot water.